Formulation of Ondansetron HCl Matrix Tablets with Microenvironmental pH Modifier for Improved Dissolution and Bioavailability under Hypochlorhydria - Anilkumar, A. (Asian Journal of Pharmaceutics (AJP), 2016)
Background: Ondansetron hydrochloride is a serotonin sub type-3 (5-hydroxytryptamine-3) receptor antagonist. It is a widely used drug for the treatment of post-operative nausea and vomiting (PONV) and chemotherapy-induced nausea and vomiting. The recommended oral dose regimen of ondansetron hydrochloride is 8 mg, three times a day up to 1 week and it is having a short biological half-life, approximately 3-5 h. Therefore, there is a need to once daily controlled release drug delivery systems to extend its therapeutic action entire the day. Aim: The main object of the present work deals with the development of pH-independent controlled release tablets of ondansetron HCl using pH modulating technique. Materials and Methods: Ondansetron HCl is a weakly basic drug belongs to BCS Class-II and it is showing distinct pH-dependent solubility. The solubility exhibits high solubility at low pH (pH 1.2) at 37Â°C (23.3 mg/ml); however, it exhibits poor solubility at higher pH (6.8 pH phosphate buffer) at 37Â°C (0.036 mg/ml). The major limitation of the drug was found burst release in stomach pH 1.2 and highly precipitation in intestinal pH (pH 6.8 phosphate buffer). The formulator is challenging to develop a controlled release formulation of constant drug release in the entire gastrointestinal tract. Matrix tablets were prepared by direct compression technique using high viscosity grade polymer (Methocel K100M), along with pH modifier for the maintenance of constant acidic microenvironment at the surface of the tablet. A 32 full factorial design was used to study the effect of pH modulating agent and optimization of ondansetron matrix tablets. Optimized formulation characterized by DSE, X-ray diffraction, and Fourier transform infrared studies was found not having any interaction with polymer and drug. Results: The release rates from formulated matrix tablets were studied at (pH 1.2) for 2 h followed by (pH 6.8). Methocel K100M with fumeric acid based matrix tablets effectively overcome pH-dependent solubility, drug release was found to be extended up to 24 h with >90% of drug release; there was a vast different between in the pharmacokinetic parameters, area under the curve, Ke, and Tmax of the optimized matrix tablets, indicating there comparable controlled pH-independent release effect. It is a potential approach for pH-independent controlled release is well supported by in-vivo pharmacokinetic studies. Conclusion: The results of in-vivo studies discovered that the optimized formulation with pH modulating agent exhibits a pH-independent controlled release of ondensetron HCl.